Curating exhausted commodities: A case study of We Buy White Albums - Taylor, Iain A. (Popular Music History, 2021)
While there has been growing interest in the curation and exhibition of popular music ephemera in recent years, such exhibitions have tended to focus on propagating canonical accounts, or on the telling of local or social histories. This article considers a different form of popular music curation, one driven not by a desire to preserve, but rather with the revaluing of so-called ‘exhausted commodities’—damaged, degraded and defaced artefacts which would otherwise be discarded. Focusing upon the case study of We Buy White Albums—an ongoing collection and exhibition by New York-based collector, curator and artist Rutherford Chang—this article explores the complexities associated with such notions of curation in the context of music-based commodities, and the potential for curatorial recontextualizations of damaged, defaced and degrading artefacts as a means of exploring hidden histories of popular music.